Characterization of the N- terminal domain of Mre11 protein from rice (OsMre11) Oryza sativa. (January 2021) - Nair, Anuradha; Pillai, Vinayaki S.; Chittela, Rajani Kant
Highlights: N- terminal region of rice Mre11, which represents both the nuclease and DNA binding domains was cloned and purified. The purified protein showed binding activity with dsDNA, ssDNA and G-quadruplexes. OsMre11 protein showed exonuclease activity only in presence of Mn 2+ . Endonuclease activity was enhanced in the presence of Mn 2+, Mg 2+ and Ca 2+ . Abstract: Chromosomal breaks occur in the genome of all living organisms upon exposure to ionizing radiation, xenobiotics and as intermediates during normal cell cycle progression. Most of the information on DNA repair process has emerged from bacteria, human, mice, and yeast while information on plant DNA repair genes and proteins is limited. Among other DNA repair proteins, MRE11 forms the core of the MRN (M re11-R ad50-N bs1) complex and is the first responder to double strand breaks (DSBs), promotes repair either by Non-Homologous End Joining (NHEJ) or Homologous Recombination (HR). Till date, MRE11 has not been biochemically characterized from plant systems. Here, we report the in vitro biochemical activities of Oryza sativa MRE11. We cloned and purified the N- terminal region of OsMre11, which represents both the nuclease and DNA binding domains. The N- terminal end of OsMre11-N protein (∼55.0 kDa) showed binding activity with dsDNA, ssDNA and G-quadruplex DNA. Tryptophan fluorescence analysis also showed that OsMre11-N protein binds to ssDNA, dsDNA and G4 DNA in a protein concentration dependant manner. Additionally, OsMre11 protein showed exonuclease activity only in the presence of Mn 2+ . A protein concentration dependant endonuclease activity also was observed and was enhanced in the presence of Mn 2+, Mg 2+ and Ca 2+ . Put together, OsMre11 has properties similar to its counterparts in yeast and humans and may play an important role in cellular response to DNA damage in plants, especially rice.